Dam failure in the light of flood and climate change: a review in case study of the Wivenhoe Dam, Brisbane Australia. - Jeet Chand; Farjana Akhter (Journal of Hydraulic Structures)
Research on multi-dimensional aspects of dam engineering is gaining momentum because of massive flood destructions in lives, ecosystem and development including Wivenhoe dam flood in 2011, Oroville dam’s spillway incident 2017 and the Europe’s widespread flooding in 2021. The aim of this study is to capture and review research activities in dam science. A case study of the Wivenhoe dam Brisbane Australia, focusing on its design, catchment, water storage and flood mitigation capacity, management procedure, climate change and historical rainfall pattern has been carried out to conclude why such a catastrophic flood event happened in Brisbane in January 2011. Reviewed literatures throughout the world indicated that dam failures are primarily associated with improper design, inadequate monitoring in construction period and poor management (operational) practices. In the case of the Wivenhoe dam flood, the report of the Flood Commission of Inquiry Australia was that the dam was operated so that its flood mitigation was near optimal. Whilst the operators were found to be at fault for not following the Operation Manual, it was found that the manual was confusing and difficult to follow, and therefore, they were cleared of all liability. Hence, it is difficult to conclude what would have actually happened if the Wivenhoe dam operators had released more water earlier, author’s reasoned outlook about the flood mitigation measures used at the time is to ask the question “was reasonable discretion” used during the flood.